If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(6y + -4) + 19 = 3(4y + 4) + 7 Reorder the terms: 5(-4 + 6y) + 19 = 3(4y + 4) + 7 (-4 * 5 + 6y * 5) + 19 = 3(4y + 4) + 7 (-20 + 30y) + 19 = 3(4y + 4) + 7 Reorder the terms: -20 + 19 + 30y = 3(4y + 4) + 7 Combine like terms: -20 + 19 = -1 -1 + 30y = 3(4y + 4) + 7 Reorder the terms: -1 + 30y = 3(4 + 4y) + 7 -1 + 30y = (4 * 3 + 4y * 3) + 7 -1 + 30y = (12 + 12y) + 7 Reorder the terms: -1 + 30y = 12 + 7 + 12y Combine like terms: 12 + 7 = 19 -1 + 30y = 19 + 12y Solving -1 + 30y = 19 + 12y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12y' to each side of the equation. -1 + 30y + -12y = 19 + 12y + -12y Combine like terms: 30y + -12y = 18y -1 + 18y = 19 + 12y + -12y Combine like terms: 12y + -12y = 0 -1 + 18y = 19 + 0 -1 + 18y = 19 Add '1' to each side of the equation. -1 + 1 + 18y = 19 + 1 Combine like terms: -1 + 1 = 0 0 + 18y = 19 + 1 18y = 19 + 1 Combine like terms: 19 + 1 = 20 18y = 20 Divide each side by '18'. y = 1.111111111 Simplifying y = 1.111111111
| 3(2y-4)+18=4(3y+1)+1 | | x^2+y^2-z=1 | | 7x-3=2x-5 | | 14x-20-13x=-14 | | 6x+7x-76=95-6x | | 105=(p^2-p) | | -18x-13=15x-4 | | x^2-37x-120=0 | | s=(p^2-p) | | 8x+4=4x+6 | | 9(x+4)+2=-9(x-8)-6 | | 7x+3=6(x+8)-8 | | 8c^2-24c+16=0 | | x+5x=-48 | | (x+3)(x+3)=-4x-15 | | p^2-64=0 | | 5.2x=29.64 | | -4x+1=21 | | p^2+1p=0 | | 2z(3z-1)=9z-3 | | p(p-16)=-48 | | x^2=1x+90 | | 2x-0.1=6.6x-37.82 | | -6y+4(6y-6)=-5+7(1-y) | | 1(x-7)-6=-4(x+8) | | 2(4x+1)=4x-12 | | 5x+2=3x+1 | | 11(x-6)-6=31x-232 | | -4(x+3)+174=32+22 | | 0.2(10x-15)=0.25(12x-8) | | 4x-20-13x=-14 | | (X-3)2-16=0 |